2018
DOI: 10.17265/2328-7136/2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-tuberculosis Activity of Total Crude Extract of Echinops Amplexicaulis against Multi-drug Resistant Mycobacterium Tuberculosis

Abstract: Background: TB (Tuberculosis) is the second leading killer infectious disease after HIV (human immunodeficiency virus). Its incidence is worsened by development of multi-drug resistant and extensive drug resistant TB strains. Available treatment regimens are expensive, toxic and lengthy resulting to problems of non-adherence and inadequate response. Medicinal plants on the other hand may offer hope for developing alternative medicine for treatment of TB. This study evaluated the anti-tuberculosis activity of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…This is in line with a previous study by Najem et al, 45 who reported saponins, alkaloids, tannins, and flavonoids found in methanol extracts of E. amplexicaulis, but phytosterols and phenols were absent. Kevin et al 9 found small amounts of tannins and saponins in E. amplexicaulis crude extract but no flavonoids, in contrast to the current study. The difference might be due to soil content, geographical area, seasons of plant collection, plant parts, and growth stage of the plants.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is in line with a previous study by Najem et al, 45 who reported saponins, alkaloids, tannins, and flavonoids found in methanol extracts of E. amplexicaulis, but phytosterols and phenols were absent. Kevin et al 9 found small amounts of tannins and saponins in E. amplexicaulis crude extract but no flavonoids, in contrast to the current study. The difference might be due to soil content, geographical area, seasons of plant collection, plant parts, and growth stage of the plants.…”
Section: Discussioncontrasting
confidence: 99%
“…7,8 Echinops amplexicaulis ("Kosorruu Harree" in Afan Oromo) belongs to the family Asteraceae and its species are found in Eastern and Southern Europe, Tropical North and East Africa, and Asia. 9 Traditional medicine practitioners in Uganda used the entire root of this plant to treat HIV/AIDS and related conditions. 10 This plant is also used to treat ulcerative lymphangitis and hepatitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the tested strains, M. tuberculosis (H37Rv) showed higher sensitivity to the ether root extract of E. giganteus and methanolic extract of E. amplexicaulis Oliv. with MIC of 12 µg/mL and 32 µg/mL, respectively (Tekwu et al, 2012; Kevin et al, 2018). The methanolic root extract of E. amplexicaulis also showed a promising effect against a multidrug-resistant strain of M. tuberculosis with a MIC of 50 µg/mL (Kevin et al, 2018).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…with MIC of 12 µg/mL and 32 µg/mL, respectively (Tekwu et al, 2012; Kevin et al, 2018). The methanolic root extract of E. amplexicaulis also showed a promising effect against a multidrug-resistant strain of M. tuberculosis with a MIC of 50 µg/mL (Kevin et al, 2018). The ethanolic root extract and essential oils obtained from E. kebericho Mesfin showed relatively strong effect against Staphylococcus aureus (Ameya et al, 2016) and Klebsiella pneumoniae (Belay et al, 2011).…”
Section: Biological Activitiesmentioning
confidence: 99%